Properties of un-torrefied and torrefied poplar plywood (PW) and medium density fiberboard (MDF) - Spirchez Cosmin; Lunguleasa Aurel; Popescu Carmen Mihaela; Avram Anamaria; Ionescu Constantin Stefan (Applied Sciences Revista, 2023)
In a context where there is an increasing need for thermal treatments of wooden products, the current research contributes a description of the torrefaction treatment of two of the composite wood materials available on the international market. The present paper presents the importance of the torrefaction process for poplar plywood and medium-density fiberboard. In this paper, the positive aspects of the torrefaction process (decrease in water absorption, thickness swelling and shrinkage, and color) but also the negative aspects of mechanical resistance to static bending are presented. Poplar plywood (PW) and medium-density fiberboard (MDF) panels, with the initial dimensions of 2000 x 1250 mm, were used. From these, 300 x 300 mm samples were cut and torrefied using two different temperatures (170 and 190 degrees C) and two different periods (for 1 and 2 h). After the treatment, the samples were cut in different sizes (as necessary for each type of evaluation method) from different zones of the panels and used to evaluate the water absorption and thickness swelling, to determine their modulus of rupture, roughness, and color changes. The obtained results emphasize that the mass loses increase at high temperature as the main disadvantageous characteristics of torrefaction. Also, while the calorific power increases with the increase in the parameters of the torrefaction regime, the hygroscopicity and some mechanical properties of the material simultaneously decrease.